Low-cost Sensors Based on the GMI Effect in Recycled Transformer Cores - Jantaratana, Pongsakorn (Molecular Diversity Preservation International (MDPI), 2008)
Sensors based on the giant magnetoimpedance (GMI) effect in silicon steels were constructed. Strips of silicon steels (0.500 mm-thick, 35.0 mm-long) with widths ranging from 0.122 to 1.064 mm were cut from recycled transformer cores. Since a maximum GMI ratio of 300% and a maximum field sensitivity of 1.5%/Oe were observed in a 1.064 mm-wide sample at 200 kHz, the 1.064 mm-wide strips were chosen as sensing elements in a slot key switch, angular velocity sensor, current sensor and force sensor. The sensing elements were integrated into electronic circuits and the changes in impedance were monitored. Variations in voltage due to these changes were typically small and must therefore be amplified by the electronic circuits. For the current sensor and force sensor, the variation in the voltage drop across the GMI sensing element had non-linear variations with either current or force and a conversion formula from a computer program was therefore needed. The performance of the systems was tested. These sensing systems were stable, highly sensitive, hysteresis-free and could be produced on a mass scale. Based on their GMI effect, the silicon steels are versatile alternative low-cost sensors.